Telaah Kritis Nilai-nilai Kebudayaan Islam “Studi Kasus Tradisi Ramadhan & Idul Fitri di Desa Pageraji Kabupaten Banyumas” - Achmad, Fatoni; Putri, Faiq Fauziya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2019)
In doing good deeds, each region in the world has its own characteristics. The custom then experienced a mix with Islamic traditions which ultimately created a harmony without leaving the applicable Shari'a. Acculturation of local culture with Islamic culture also occurred in Pageraji Village, Cilongok District, Banyumas Regency, Central Java. The Pageraji village community has a number of customs related to Islam that are still enduring today. The tradition is that the tarawih prayer time is slightly different from other regions, which is between 22:00 - 23:00, and the tradition of eating together and grave pilgrimage after the Eid prayer